2018
DOI: 10.23958/ijirms/vol03-i05/05
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic Surgeries of Lower Limb under Combined Femoral and Sciatic Nerve Block: A Comparative Study in RMCH & RC

Abstract: The best option for life-saving operations is regional block anesthesia where both general and central neuraxialanesthesia are risky. It does not require fasting, special preparation, or preoperative optimization and can be given in emergency conditions.[1] Also peripheral nerve blocks (PNBs) are preferred for lower limb surgeries and orthopaedic surgeries because of peripheral location of surgical site and the potential to block pain pathways at multiple levels.[2] Furthermore, better cardio respiratory stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
(15 reference statements)
1
1
0
Order By: Relevance
“…They found that anesthesia was attained within 12 to 18 min from the injection of the anesthetic agent. The overall durations of sensory and motor nerve block in this study were 14 and 12 hours, respectively, confirming that SF/NB was an effective and safe method of anesthesia, particularly for patients at risk [7].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…They found that anesthesia was attained within 12 to 18 min from the injection of the anesthetic agent. The overall durations of sensory and motor nerve block in this study were 14 and 12 hours, respectively, confirming that SF/NB was an effective and safe method of anesthesia, particularly for patients at risk [7].…”
Section: Discussionsupporting
confidence: 73%
“…The lumbar plexus, through its L2-L4 anterior roots, is responsible for innervating the anterior and medial portion of the thigh by means of the major femoral and obturator nerves. The sacral plexus is the point where the sciatic and posterior cutaneous nerves of the thigh originate [7]. As these nerves transfer the majority of sensory and motor impulses throughout the entire length of the lower extremities, their blockade, which will be regarded as LP/NB in this manuscript, would serve as an effective method in the induction of anesthesia [8].…”
Section: Introductionmentioning
confidence: 99%